중복 자궁경부와 질중격을 가진 완전 중격 자궁의 변형 - 신미선; Mi Sun Shin; 한경희; Kyung Hee Han; 김수아; Su Ah Kim; 정희정; Hee Jung Jung; 황은주; Eun Ju Hwang; 지병철; Byung Chul Jee; et al. (Obstetrics & gynecology science, 2010)
현재의 분류에는 포함되지 않는 드문 형태의 뮐러관 기형이 최근 보고되고 있다. 30세의 미산부 여성이 2년간의 불임을 주소로 내원하였다. 복강경상 자궁 저부 및 난관의 상태는 정상이었다. 자궁경상 중복 자궁경관 및 질중격을 확인하였고 자궁 하단부에서 교통이 있는 완전 중격 자궁을 확인하였다. 오른쪽 자궁경관을 통해 자궁경하 중격제거술을 성공적으로 시행하였다. 자궁협부에 교통이 있는 중복 자궁경관 및 질중격을 가진 완전 중격 자궁의 변형된 예로서 자궁경을 통한 수술을 통해 치료될 수 있었다. Rare mullerian anomalies without any present classification were sometimes reported. A 30-year-old nulligravid woman was referred to our hospital with 2-year history of primary infertility. Laparoscopic examination revealed a relatively intact uterine fundus with both patent fallopian tubes. Hysteroscopic exam confirmed the presence of double vagina and cervix, as well as complete uterine septum with opening at the lower segment. Hysteroscopic septotomy was successfully performed through the right-sided cervix. A variant of complete septate uterus with double cervix that communicated at the isthmic portion could be successfully treated by hysteroscopic operation.